2012
DOI: 10.1093/jac/dks414
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inhibition of Trichophyton rubrum: in vitro activity and the role of oxidative and nitrosative bursts in fungal death

Abstract: Photodynamic inhibition was more efficient in promoting cell death than the antifungal cyclopiroxolamine against T. rubrum. ROS, ONOO· and NO· were important in the fungicidal activity of aPI. A suggested mechanism for this activity is that TBO is excited by LED light (630 nm), reacts with biomolecules and increases the availability of transition electrons and substrates for nitric oxide synthase, thereby increasing the oxidative and nitrosative bursts in the fungal cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 48 publications
4
60
0
1
Order By: Relevance
“…Pc 4-PDT also demonstrated an excellent safety profile in a phase 1 trial on cutaneous neoplasms (25). Although the susceptibility of T. rubrum to PDT using other photosensitizers has been extensively investigated in vitro, the mechanism of phototoxicity has not been clearly defined (2,9,(26)(27)(28). In this study, we showed that a common dose of Pc 4-PDT can induce cell death in microconidia (terbinafine-sensitive and -resistant strains of T. rubrum).…”
mentioning
confidence: 77%
“…Pc 4-PDT also demonstrated an excellent safety profile in a phase 1 trial on cutaneous neoplasms (25). Although the susceptibility of T. rubrum to PDT using other photosensitizers has been extensively investigated in vitro, the mechanism of phototoxicity has not been clearly defined (2,9,(26)(27)(28). In this study, we showed that a common dose of Pc 4-PDT can induce cell death in microconidia (terbinafine-sensitive and -resistant strains of T. rubrum).…”
mentioning
confidence: 77%
“…The fungal cells were grown in YPD medium for 7 days at 35 to 37°C in the presence or absence of L-DOPA and suspended in PBS to achieve 1 ϫ 10 7 viable cells/ml. The final concentrations of inocula for susceptibility tests and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assays were 0.5 ϫ 10 5 to 1 ϫ 10 5 yeast cells/ml for the antifungal tests and 1 ϫ 10 6 cells/ml for the aPI tests (19,24).…”
Section: Fungal Isolatesmentioning
confidence: 99%
“…Toluidine blue (TBO) (Sigma, St. Louis, MO, USA) was used as a photosensitizer at concentrations of 70 mg/liter, 40 mg/liter, and 10 mg/liter. A light-emitting diode (LED) (Fisioled; MMoptics, São Paulo, Brazil) was used as a source of monochromatic light (19). The energy doses tested were 30 J/cm 2 , 60 J/cm 2 , and 90 J/cm 2 .…”
Section: Fungal Isolatesmentioning
confidence: 99%
See 2 more Smart Citations